Peran dan strategi kepala paud dalam meningkatkan mutu pendidikan pada masa pandemi covid-19 - Rokhadi Rokhadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The objectives to be achieved from this paper are: (1) Describe the role of the PAUD head in Improving the Quality of Education during the Covid 19 Pandemic and (2) Analyzing the strategy of the PAUD head in Improving the Quality of Education during the Covid Pandemic 19. The role of the PAUD head is very crusial in the process administration of education. PAUD as a gateway for early childhood development, of course requires professional management. In the research above, the role of the PAUD head before and during the Covid 19 pandemic there is a difference from the focus or orientation of the principal in education delivery. Before the Covid period, the role of an educator was the focus of the school principal, while during the Covid 19 pandemic, the role of administrator was the main role. However, the research results show that the principal has carried out his role well. In any condition, the role of the principal as a leader must be carried out properly. The results of research conducted on PAUD principals in the Candiroto District of Temanggung show that they have carried out their leadership roles very well and have made optimal efforts to improve the quality of education delivery.